Neurodevelopmental Outcomes of Infants Younger Than 90 Days Old Following Enterovirus and Parechovirus Infections of the Central Nervous System - de Ceano-Vivas, María; García, M. Luz; Velázquez, Ana; Martín del Valle, Fernando; Menasalvas, Ana; Cilla, Amaia; Epalza, Cristina; Romero, M. Pilar; Cabrerizo, María; Calvo, Cristina (Frontiers in Pediatrics, 2021)
Enteroviruses (EVs) and human parechoviruses (HPeVs) are a major cause of central nervous system (CNS) infection in young infants. They have been implicated in neurodevelopmental delay, however limited data are available. The aim of this study is to describe the clinical outcome of young infants and to assess and compare the medium-term neurodevelopment following CNS infections caused by EV and HPeV. A multicentre observational ambispective study was conducted between May 2013 and March 2018. Children under 3 months of age with EV or HPeV CNS infection excluding encephalitis were included. Infants were contacted one year after the acute infection and their neurological development was evaluated using the Ages and Stages Questionnaire-3 (ASQ-3). If any area assessed was abnormal during the first round of tests, a second round was completed 6 to 12 months later. Forty-eight young infants with EV and HPeV CNS infection were identified: 33 (68.8%) were positive for EV and 15 (31.3%) for HPeV. At first assessment 14 out of 29 EV (48.3%) and 3 out of 15 HPeV (20%) positive cases presented some developmental concern in the ASQ-3 test. EV-positive infants showed mild and moderate alteration in all domains analysed and HPeV-positive infants showed mild alterations only in gross and fine motor domains. Significant alterations in communication were observed in EV-positive but not in HPeV-positive infants (31% vs 0%, p=0.016). At second assessment 4 out of 13 EV-positive patients (30.8%) showed mild to moderate concerns in communication and gross motor function domains and 3 out of 13 (23.1%) showed significant concern in fine motor function. Although CNS infections without associated encephalitis are generally assumed to be benign our study shows that at a median age of 18 months almost half of the EV-infected infants (48.3%) and 20% of HPeV-positive infants presented some developmental concern in the ASQ-3 test. We recommend monitor the neurological development of infants during the first years of life after HPeV CNS infection and especially after EV CNS infection, even in mild cases, for an early intervention and stimulation of psychomotor development if necessary.